Leonid Schneider calls Springer Nature's Science and Engineering Ethics Predatory, Without Proof - Jaime A. Teixeira da Silva (Centre for Behaviour and Wellness Advocacy, 2019)
In the world of academic publishing, to refer to a journal or publisher (or any other scholarly entity) as "predatory" carries with it a very serious and negative connotation, and can damage its reputation if that claim is made in public. If such a claim is supported by clear evidence, then it becomes a valid critical opinion because it is substantiated. Even if others share different opinions, the original claim cannot be false if clearly substantiated by evidence. However, if such a claim is made without solid support, then such a claim can be defamatory. Academics are weary of the nature of such claims from the Jeffrey Beall era. Between May and December of 2017, Leonid Schneider, currently one of science's most vocal watchdogs, Tweeted on several occasions that Springer Nature's Science and Engineering Ethics (SEE) was "predatory", in one Tweet even stating that "They are deeply unethical crooks at Science & Eng Ethics!" These are not light claims to be made in public. Moreover, Twitter is not simply a private communication medium, it is a powerful disseminative social media tool that is used by academics, and others, to give maximum exposure to a message. In this case, Tweets were likely made to cause reputational damage. Academia has entered a new phase in its evolution where polite communication about the issues to save the image of the for-profit publishing model is being tested by select individuals or groups, who sacrifice political correctness in the name of truth. If Schneider were to provide clear proof of his claims that SEE is predatory, then this would rock the world of ethics publishing, because SEE represents one of the most established academic ethics journals globally, ranked third based on its Clarivate Analytics journal impact factor. On September 16, 2017, the author contacted Schneider to request a full and thorough list of properties that led him to make these accusations in public. In that email, the SEE co-editors-in-chief, Raymond Spier and Stephanie Bird, Springer Nature, COPE and other related individuals were copied, with a formal request to offer feedback. Almost two years after that email, not a single entity has ever responded. Spier deceased at the end of April 2018, leaving a vacuum in this challenge by Schneider on SEE. This paper offers some perspectives about this case, and the wider implications of making accusations in public, especially using Twitter, which is now clamping down on social media aggression, of a potentially defamatory nature, without proof or substantiation.